CONTACT MAT: DEVICE FOR MEASURING ASYMMETRY IN LOWER LIMBS (Fiep Bulletin - online, 2013)
Lateral asymmetries concerning the magnitude of muscle strength are often found in lower limbs (LL) and are related to the preference of the limbs to be used (dominant and non-dominant) and the motor performance. How many sports require propulsion unilateral in directions horizontal and vertical, the unilateral assessment may be a procedure to assess the asymmetries of LL. The double force platform (DFP) is a device more suitable for diagnosing imbalances in LL, being considered "gold standard". However, it has become inaccessible for many coaches BY high financial cost. Already the contact mat (CC) allows the verification and control the performance of jumps, through the time of flight, with a low cost relatively. Thus, this study aimed to verify if the CC is a device capable of diagnosing asymmetries related to the force magnitude between LL in countermovement jump as the DFP. 29 volunteers were randomly evaluated in both tests. The jump height (HS) on the CC and impulse (IP) generated in DFP of both lower limbs were analyzed by percentage of asymmetries and is considered lateral asymmetry percentages above 15%. Each volunteer performed 3 trials with 2 minutes rest between jumps and one week between tests. In double force platform, the lower limbs were tested simultaneously, already on the carpet unilaterally. To assess the relationships between the means variables HS and IP to diagnose asymmetries, the coefficient of contingency (C) was used by SPSS 13.0. The result was C = 0.62, p = 0.01 was satisfactory and showed a moderate association between tests. Conclusion: The contact mat showed to be also an instrument able to identify asymmetries in the magnitude of the strength of LL when compared with double force platform. We suggest further studies with similar design to that, though involving athletes, sedentary individuals, among others.